Quercetin suppresses the progression of HBV-associated hepatocellular carcinoma by modulating the EGFR signaling pathway - Zhijuan Wang; Jinzhen Huang; Danping Huang; Rui An; Guangdong Tong; Weiqu Yuan; Mianmian Liao; Qiusheng Zhong (PLoS ONE, 2026)
Background Quercetin, a bioactive flavonoid compound widely present in medicinal and edible plants, has demonstrated therapeutic potential against hepatocellular carcinoma (HCC). However, its specific mechanism in hepatitis B virus-associated hepatocellular carcinoma (HBV-HCC) remains unclear. This study aims to systematically elucidate the efficacy and molecular mechanisms of quercetin against HBV-HCC. Methods Integrated in vitro and in vivo experimental models were employed. The inhibitory effects of quercetin on HCC cell viability, proliferation, clonogenicity, and migration were assessed through CCK-8, EdU, colony formation, and scratch assays. Network pharmacology and molecular docking were integrated to identify potential targets of quercetin within HCC. Lentiviral transfection was used to construct HCC cell lines overexpressing HBx and EGFR, with key signaling pathways verified via Western blot. Additionally, a xenograft mouse model was established, and the EGFR inhibitor osimertinib was combined to evaluate quercetin’s therapeutic efficacy and underlying mechanisms in HBV-HCC. Results Through an extensive analysis of the target interaction network analysis of quercetin in HCC, this study identified and prioritized 29 potential therapeutic targets, with the EGFR recognized as the principal target molecule. The results of molecular docking experiments indicated that both EGFR and GSK3β exhibited good binding affinity. Subsequent in vitro studies revealed that quercetin substantially suppresses the growth and migration of HBV-HCC cells. It achieves this by dose-dependently suppressing EGFR, thereby attenuating the signaling of the downstream PI3K/AKT/GSK3β axis and concurrently reversing the epithelial-mesenchymal transition (EMT) process. In vivo investigations, complemented by control studies using EGFR inhibitors, further validate that quercetin exerts its anti-tumor effects against HBV-HCC through specific targeting of EGFR and the suppression of the EMT program. Conclusion This research validates the therapeutic effectiveness of quercetin in inhibiting HBV-HCC and elucidates the molecular mechanisms responsible for its action. Mechanistically, quercetin inhibits the PI3K/AKT/GSK3β signaling axis by targeting EGFR, thereby reversing the EMT process and ultimately impeding HBV-HCC progression. These critical outcomes provide a novel theoretical foundation for the targeted therapy of HBV-HCC using quercetin.